Differences in Physical Activity Density Between Pregnant Women with Gestational Diabetes Mellitus (GDM) and Normal (Non-GDM) Pregnant Women: A Comparative Study - Rohmatul Ummah; Muhammad Ilham Aldika Akbar; Bambang Purwanto (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Background: Gestational diabetes mellitus (GDM) is a condition of impaired glucose tolerance that leads to high blood sugar levels and is diagnosed for the first time during pregnancy, with varying degrees of severity. Insufficient physical activity is one of the top global risk factors for premature death. During pregnancy, a lack of physical activity and excessive weight gain are independent risk factors for maternal obesity and related complications, including gestational diabetes mellitus (GDM).Objectives: The aim of this study was to compare the physical activity density between pregnant women diagnosed with gestational diabetes mellitus (GDM) and those with normal pregnancies.Methods: This study utilized an observational analytical approach with a comparative design. A purposive sampling technique was employed, with 32 participants in the case group and 32 in the control group. The research was conducted between August and October 2024 at the Obstetrics and Gynecology clinic of Airlangga University Hospital. Data were analyzed using the non-parametric Mann-Whitney Test.Results: The analysis using the Mann-Whitney Test showed a significant p-value of 0.002, indicating a difference in the physical activity density between pregnant women with gestational diabetes mellitus (GDM) and those with normal pregnancies.Conclusion: Pregnant women without gestational diabetes mellitus (GDM) have higher physical activity density compared to those with gestational diabetes mellitus (GDM). It is suggested that future research adopt an experimental approach, especially focusing on interventions to promote physical activity during pregnancy.